2021
DOI: 10.3390/microorganisms9112389
|View full text |Cite|
|
Sign up to set email alerts
|

Diversity and Hydrocarbon-Degrading Potential of Deep-Sea Microbial Community from the Mid-Atlantic Ridge, South of the Azores (North Atlantic Ocean)

Abstract: Deep-sea sediments (DSS) are one of the largest biotopes on Earth and host a surprisingly diverse microbial community. The harsh conditions of this cold environment lower the rate of natural attenuation, allowing the petroleum pollutants to persist for a long time in deep marine sediments raising problematic environmental concerns. The present work aims to contribute to the study of DSS microbial resources as biotechnological tools for bioremediation of petroleum hydrocarbon polluted environments. Four deep-se… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
1
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(3 citation statements)
references
References 71 publications
0
1
0
Order By: Relevance
“…There were more low temperature petroleum hydrocarbon degrading strains isolated from S39 than from S02. Hydrocarbon degrading microorganisms were more abundant in the deep sea basin due to the accumulation of organic matter and low temperature (Tomasino et al, 2021).…”
Section: Screening and Identification Of Petroleum Hydrocarbon Degrad...mentioning
confidence: 99%
See 1 more Smart Citation
“…There were more low temperature petroleum hydrocarbon degrading strains isolated from S39 than from S02. Hydrocarbon degrading microorganisms were more abundant in the deep sea basin due to the accumulation of organic matter and low temperature (Tomasino et al, 2021).…”
Section: Screening and Identification Of Petroleum Hydrocarbon Degrad...mentioning
confidence: 99%
“…Recent studies demonstrated there were plenty of hydrocarbon degrading bacteria in the Mariana Trench (Liu J. et al, 2019). Although several petroleum hydrocarbon degrading bacteria had been isolated from deep-sea sediments (Gao et al, 2015;Tomasino et al, 2021), the current research on their degradation potential was still limited.…”
Section: Introductionmentioning
confidence: 99%
“…The effect of biostimulation on microbial community abundance, structure, dynamics, and the metabolic potential for oil hydrocarbon degradation in oil-contaminated Arctic seawater were studied by Nõlvak et al [ 6 ]. The second paper, by Tomasino and co-authors [ 7 ], addressed petroleum pollution in cold, deep marine sediments. Using the deep-sea sediment samples from the North Atlantic Ocean, they identified bacterial strains with the potential for the enhanced bioremediation of petroleum hydrocarbon-polluted sediments.…”
mentioning
confidence: 99%